The role of flexibility in building the competitiveness of small and medium enterprises = Rola elastyczności w budowaniu konkurencyjności małych i średnich przedsiębiorstw - Matejun, Marek (Zielona Góra: Faculty of Economics and Management Press)
Flexibility is perceived as the key factor determining the competitiveness and a competitive edge of contemporary organizations, as it is one of the most basic qualitative features of this category of entities. Taking this into account, the author of the article decided to present and evaluate the possibilities and conditions for using flexibility in building competitiveness of SMEs. The aim of the article was achieved through conducting surveys on the sample of 61 companies from the Lodz region.
Keywords: małe i średnie przedsiębiorstwa; elastyczność; konkurencyjność; przewaga konkurencyjna; small and medium-sized enterprises; flexibility; competitiveness; competitive advantage